PENGEMBANGAN KEPROFESIAN BERKELANJUTAN GURU BAHASA MADURA MELALUI DIKLAT BAHASA DAN SASTRA MADURA DI PAMEKASAN - Fakhiroh, Eva Zakiyatul; Liska; Nurhadi, Ali; Atiqullah; Mufarrikoh , Zainatul (re-JIEM (Research Journal of Islamic Education Management), 2023)
Continuous professional development is the effort made by teachers to enhance their professionalism through established standards and the advancement of knowledge, technology, and art. The research aims to understand the management of training programs and identify the supporting and inhibiting factors of these training activities. The research adopts a descriptive-qualitative approach. Data collection techniques include interviews, observations, and documentation. Data analysis involves data reduction, data presentation, and conclusion. The research result on planning, committee formation, vision, mission, objectives, empowerment of members to become training facilitators, and collaboration with cultural experts. Organizing involves assigning tasks to eight members based on their competencies. In implementation, the training attracts Madurese language teachers from all levels, from elementary to high school, through collaboration with various parties and is conducted annually. Identified evaluations include planning, certificate issuance services, and time effectiveness. Supporting factors relate to the educational background and competency of members, the possession of laptops by all members, involvement in multiple organizations for easy information sharing, clear work programs, and adequate facilities and infrastructure. Meanwhile, inhibiting factors include stagnant grant assistance, insufficient publication techniques, and the lack of community concern for the importance of preserving local cultural heritage, especially the Madurese